Evidence and consensus based guideline for the management of delirium, analgesia, and sedation in intensive care medicine. Revision 2015 (DAS-guideline 2015) – short version - Baron, Ralf; Binder, Andreas; Biniek, Rolf; Braune, Stephan; Buerkle, Hartmut; Dall, Peter; Demirakca, Sueha; Eckardt, Rahel; Eggers, Verena; Eichler, Ingolf; Fietze, Ingo; Freys, Stephan; et al. (GMS German Medical Science, 2015)
In 2010, under the guidance of the DGAI (German Society of Anaesthesiology and Intensive Care Medicine) and DIVI (German Interdisciplinary Association for Intensive Care and Emergency Medicine), twelve German medical societies published the “Evidence-and Consensus-based Guidelines on the Management of Analgesia, Sedation and Delirium in Intensive Care”. Since then, several new studies and publications have considerably increased the body of evidence, including the new recommendations from the American College of Critical Care Medicine (ACCM) in conjunction with Society of Critical Care Medicine (SCCM) and American Society of Health-System Pharmacists (ASHP) from 2013. For this update, a major restructuring and extension of the guidelines were needed in order to cover new aspects of treatment, such as sleep and anxiety management. The literature was systematically searched and evaluated using the criteria of the Oxford Center of Evidence Based Medicine. The body of evidence used to formulate these recommendations was reviewed and approved by representatives of 17 national societies. Three grades of recommendation were used as follows: Grade “A” (strong recommendation), Grade “B” (recommendation) and Grade “0” (open recommendation). The result is a comprehensive, interdisciplinary, evidence and consensus-based set of level 3 guidelines. This publication was designed for all ICU professionals, and takes into account all critically ill patient populations. It represents a guide to symptom-oriented prevention, diagnosis, and treatment of delirium, anxiety, stress, and protocol-based analgesia, sedation, and sleep-management in intensive care medicine.
CRIS-Team Scopus Importer:2022-09-26
Keywords: Analgesia; Anxiety; Critical care; Delirium; Evidence; Germany; Guideline; Intensive care; Monitoring; Sedation; Sleep; Stress; Treatment